Exploring OOAD Concepts Through Course Projects - Kanakaraddi, Suvarna G.; Chikaraddi, Ashok K.; Naragund, Jayalaxmi G.; Sujatha, C. (Journal of Engineering Education Transformations, 2017)
This paper presents the innovative approach carried out in conducting Object Oriented Analysis and Design (OOAD) lab course for post graduate students. OOAD lab course is designed in such a way that the students will be able to analyze, design and implement the real time problems. The lab course structure involves mainly two parts; in the first part selecting problem, analyzing the requirements and designing the chosen problem. The second part focuses on implementation of the design, completed in previous phase.We discuss the methods of OOAD and applied them for implementing the real world applications. Students have implemented the projects in this lab course through which they have explored the OOAD concepts. Problem selection choice is given to the students. In the first part students have done the design of the chosen problem using OOAD and UML concepts individually. This design is done through Rational ROSE tool. In second part, group of 2 or 3 students have implemented the application using JAVA and My SQL programming language.The outcome of this course, 15 projects like hospital, restaurant, vehicle booking, inventory, hostel and placement management system, etc. have developed by the students. Thus the activity of project development has improved the design, implementation and presentation skills of students. The performances of the students are measured in Continuous Internal Evolution (CIE) and Semester End Exam(SEE).